Impact of different types of entrepreneurial alertness on entrepreneurial opportunities identification - Li, Zhenning; Jiang, Bing; Bi, Shulei; Feng, Jing; Cui, Qianyi (Frontiers in Psychology, 2022)
In the context of resource constraints, how different dimensions of entrepreneurial alertness affect the entrepreneurial opportunity recognition of new ventures is an important issue worth studying. From entrepreneurial cognition theory and bricolage theory perspectives, we systematically investigate the intrinsic relationships among entrepreneurial alertness, entrepreneurial bricolage, entrepreneurial passion, and entrepreneurial opportunity recognition. Further, it explored the intrinsic mechanism of role in exploring entrepreneurial opportunity recognition. This study applied stepwise regression analyses and the Bootstrap method to test the hypotheses on a sample of 295 questionnaires of the new venture. The findings revealed that entrepreneurial alertness is positively related to entrepreneurial opportunity recognition. Entrepreneurial bricolage is positively related to entrepreneurial opportunity recognition. Entrepreneurial bricolage partially mediates between entrepreneurial alertness and entrepreneurial opportunity recognition. Entrepreneurial passion positively moderates the relationship between entrepreneurial bricolage and entrepreneurial opportunity identification. The study guides new ventures to enhance entrepreneurial alertness and reasonably use entrepreneurial bricolage to explore entrepreneurial opportunities.